Tailoring Disordered/Ordered Phases to Revisit the Degradation Mechanism of High‐Voltage LiNi0.5Mn1.5O4 Spinel Cathode Materials. (26th February 2022) - Sun, Huabin; Hu, Anyang; Spence, Stephanie; Kuai, Chunguang; Hou, Dong; Mu, Linqin; Liu, Jue; Li, Luxi; Sun, Chengjun; Sainio, Sami; Nordlund, Dennis; Luo, Wei; et al.
Abstract: In the spinel oxide cathode family, LiNi0.5 Mn1.5 O4 (LNMO) shows a high operating voltage (≈4.7 V vs Li/Li + ) and excellent Li‐ion mobility with stable 3D conducting channels. Ni/Mn cation disordered and ordered phases usually coexist in LNMO materials, and they have distinct structural and electrochemical properties, resulting in different battery performances for LNMO materials with different phase compositions. Identifying the correlation between phase compositions and electrochemical properties is of significance to the improvement of battery performance and understanding of degradation mechanisms. Herein, the disordered/ordered phase compositions in LNMO materials are tailored by post‐annealing strategies and their impacts on electrochemical performance and degradation mechanisms from the surface to the bulk are systematically investigated. The ordered phase increases rapidly as Mn 3+ is oxidized to Mn 4+ through a post‐annealing process. LNMO with an intermediate fraction of disordered and ordered phases gives rise to improved cycling stability. This article further reports that a high ordered phase fraction can preferentially protect Ni from dissolution during cycling. However, these results suggest that the transition metal dissolution and surface structural change of LNMO do not exhibit a direct correlation with cycling stability. These results indicate the capacity fading mainly correlates with the bulk structural distortion, leading to decreased Li‐ion kinetics. Abstract : The disordered/ordered phase ratio in LiNi0.5 Mn1.5 O4 (LNMO) cathode materials is tailored and the degradation mechanism from the surface to the bulk of LNMO is systematically studied using synchrotron and neutron analyses. The cycling stability of LNMO highly depends on bulk structural changes and less on surface degradation.